Early childhood teachers’ understanding and perceptions of augmented reality (AR) to enhance learning - Connie Shin @ Connie Cassy Ompok; Jusiah Idang; Musirin Mosin; Liu Qinghua; Priscilla Kyle Payne; Noraina binti Noraidi (Journal Of Electrical Systems, 2024)
The rapid growth and ongoing evolution of technology and innovation in the current digital era have become wellestablished, driven by trends in digital transformation. The convergence of technological advancements calls for proactive measures in Early Childhood Education. This study explores the potential integration of Augmented Reality (AR) technology into Malaysia's Early Childhood Education and its effects on learning. A survey involving 200 early childhood teachers across Sabah, Malaysia, was conducted to assess their knowledge and perceptions of AR technology. The results revealed that respondents strongly understood AR technology and viewed it positively as a tool to enhance learning. The findings highlighted a positive correlation between the respondents' knowledge of AR and their willingness to incorporate it into their teaching practices.